(untitled) - McFedries, Paul (Hoboken, N.J., 2005)
The perfect guide for visual learners who are brand-new to Windows XP and want to be shown-rather than told-how to solve problems and work through tasks. Features highly visual two-page tutorials and full-color step-by-step screen shots that walk Windows newcomers through tasks such as working with files, sharing a computer, browsing the Web, using e-mail, and even creating movies. Covers new SP2 enhancements, including the new Windows Firewall and wireless interface as well as updates to Windows Update, Media Player, and Internet Explorer
Keywords: Microsoft Windows (Computer file),Microsoft Windows (file máy tính)